Practical Applications of Strength Criteria in Civil Engineering Designs for Shallow Tunnels in Weak Rock - Didi S Agustawijaya (International Journal of Technology, 2019)
A number of rock strength criteria are available for use in civil engineering designs. Although considerable uncertainty in geological conditions and variability in rock properties is involved in estimating rock mass strength, it may be necessary to divide the criteria into two categories based on rock failure behavior: linear and non-linear. In this research, both types of criteria are applied to estimate the strength of weak rock masses at five different shallow tunnel sites. The results show varying strength values. The variation in weak rock properties affects the variability of rock strength, depending on the frictional properties for the linear criterion, and on the geological strength index (GSI) for the non-linear criterion. Confinement may also influence both criteria, but the estimated strength of the non-linear criterion is still low for weak rock when the GSI is low. Accordingly, the implication of these variations and uncertainties in rock properties is that the linear criterion may be practically suitable for tunnelling at shallow depths where instability is mostly due to gravity loads. The criterion tends to provide moderate, conservative rock mass strength estimations for this type of tunnel, since shear mechanisms may dominate rock mass failures around it.